Through the looking glass: self-reassuring meta-cognitive capacity and its relationship with the thematic content of voices - Connor, Charlotte; Birchwood, Max (Frontiers in Human Neuroscience, 2013)
Aims: To examine the self-critical thoughts and self-reassuring meta-cognitive capacity of those who hear voices and explore whether they are associated with the theme of voice content and appraisals of voice power and voice expressed emotion. Method: A cross-sectional design was used, combining semi-structured interviews and self-report measures. Data on symptomatology, self-critical thoughts and self-reassuring meta-cognitive capacity, thematic voice content, and appraisals of voice power and expressed emotion were collected from 74 voice-hearers in Birmingham, UK. Results: Common themes of voice content reflected issues of shame, control, and affiliation. Controlling content was the most prevalent theme, however, no significant predictor of this theme was found; shaming thematic voice content linked with reduced capacity to self-reassure following self-critical thoughts. Voice-hearers with the greatest level of self-critical thoughts appraised their voices as powerful and high in voice expressed emotion. Conclusions: Findings suggest that voice-hearers self-critical thoughts are reflected in the type of relationship they have with their voice. However, access to self-reassuring meta-cognitive capacity may serve as a protective factor for those who hear voices, resulting in more benign voice content. These findings highlight the importance of this specific meta-cognitive capacity and will inform future therapeutic interventions for the management of voices in this vulnerable group.